JFK revisited : the complete collection [videorecording (Blu-Ray + DVD)] - DiEugenio, James, 1952-; Stone, Oliver; Goldberg, Whoopi, 1955-; Sutherland, Donald, 1935- (Shout Factory, 2022)
Thirty years after his renowned film JFK, Oliver Stone takes viewers on a thought-provoking and eye-opening journey through recently declassified evidence in the assassination of President John Fitzgerald Kennedy. Subjects covered include the early formation of President Kennedy's foreign policy overview and his anti-colonial convictions, which put him in opposition to the Eisenhower administration, the CIA, and the Pentagon.